2017
DOI: 10.1007/s12011-017-1216-7
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Toxic Elements in Edible Crops from Seleniferous Area (Punjab, India)

Abstract: The primary objective of the present study was to assess the level of selenium and toxic trace elements in wheat, rice, maize, and mustard from seleniferous areas of Punjab, India. The content of selenium (Se) and toxic trace elements, including aluminum (Al), arsenic (As), cadmium (Cd), mercury (Hg), nickel (Ni), lead (Pb), and tin (Sn), in crop samples was assessed using inductively coupled plasma mass-spectrometry after microwave digestion of the samples. The obtained data demonstrate that cultivation of cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Bernat et al (2014) reported that Ni toxicity is associated with changes in phospholipids, and although the use of Se improved wheat growth, it did not reduce its negative effect on phospholipids profile. Skalnaya et al (2018) showed that growing wheat in selenium-rich soil reduces the content of toxic metals such as Ni and Pb in roots and shoots. Zinc oxide (ZnO) nanoparticles prevented the adverse effects of cadmium stress in the plant but caused the accumulation of Cd in the root and stem tissues of mung beans (Roshid et al, 2022).…”
Section: Interaction Se Zn Biofortification With Toxic Metals Such As...mentioning
confidence: 99%
See 1 more Smart Citation
“…Bernat et al (2014) reported that Ni toxicity is associated with changes in phospholipids, and although the use of Se improved wheat growth, it did not reduce its negative effect on phospholipids profile. Skalnaya et al (2018) showed that growing wheat in selenium-rich soil reduces the content of toxic metals such as Ni and Pb in roots and shoots. Zinc oxide (ZnO) nanoparticles prevented the adverse effects of cadmium stress in the plant but caused the accumulation of Cd in the root and stem tissues of mung beans (Roshid et al, 2022).…”
Section: Interaction Se Zn Biofortification With Toxic Metals Such As...mentioning
confidence: 99%
“…(2014) reported that Ni toxicity is associated with changes in phospholipids, and although the use of Se improved wheat growth, it did not reduce its negative effect on phospholipids profile. Skalnaya et al. (2018) showed that growing wheat in selenium-rich soil reduces the content of toxic metals such as Ni and Pb in roots and shoots.…”
Section: Application Of Selenium and Zinc For Crop Biofortificationmentioning
confidence: 99%
“…Trace minerals, such as copper, zinc, iron, iodine, manganese, and chromium, are required in smaller amounts by the body but are also important for animal health [ 2 ]. However, certain amounts of toxic elements including arsenic, mercury, cadmium, and lead, adversely affect the body [ 3 ].…”
Section: Introductionmentioning
confidence: 99%